2021
DOI: 10.1007/s10561-021-09908-w
|View full text |Cite
|
Sign up to set email alerts
|

Management of regional bone bank during declaration of a state of emergency concerning the COVID-19 in Japan

Abstract: Bone banks are necessary for providing biological allografts for a series of orthopedic procedures. As nations cope with new realities driven by the 2019 coronavirus disease (COVID-19) pandemic, health-care providers, institutions, and patients share a particular concern about the effect of COVID-19 on organ donation and transplantation. Here, we describe the management of the Kitasato University Bone Bank during the state of emergency declared in response to COVID-19. Living donors received pre-operative scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, tissue banks all over the world established strict preventive measures, or in some cases stopped collecting samples. On the other hand, at the moment, no documented reports have proved any COVID-19 infection following tissue transplantation [ 20 , 21 ]. We think that our results could represent a valid basis for further studies related to the possibility of bone donation in patients who suffered and healed from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tissue banks all over the world established strict preventive measures, or in some cases stopped collecting samples. On the other hand, at the moment, no documented reports have proved any COVID-19 infection following tissue transplantation [ 20 , 21 ]. We think that our results could represent a valid basis for further studies related to the possibility of bone donation in patients who suffered and healed from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the bank stopped accepting donations from deceased donors in order to protect medical personnel. Following bone allograft, none of the patients had any symptoms [ 32 ]. The same requires to be followed in our country if such a pandemic strikes in our part of the country too.…”
Section: Reviewmentioning
confidence: 99%
“…A literature review of nursing students’ attitudes found that interest in organ donation correlated with an increase in donor cards [ 21 ]. The Kitasato Bone Bank ceased donations until protocols for COVID-19 screening were implemented [ 22 ], suggesting a potential impact on other organ and tissue donation processes. Additionally, a study conducted at a Baptist hospital reported that religion appeared to provide comfort and relief for donor relatives [ 23 ].…”
Section: Introductionmentioning
confidence: 99%